Review of companies and drug classes in the 2007–2011 antihypertensive patent literature. (March 2012) - Carpino, Philip A; Flynn, Declan
Hypertension, defined as elevated systolic blood pressure and/or diastolic blood pressure generally greater than 140/90 mmHg, is a significant risk factor for cardiovascular outcomes such as arterial aneurysm, myocardial infarction and stroke, and for nonvascular conditions such as Alzheimer's disease. The prevalence of the disease is rapidly increasing both in the USA and in the rest of the world. Hypertension can be managed to a degree through behavioral changes (e.g., reduction in salt intake and loss of excess body weight). When lifestyle changes fail, pharmacological therapy provides benefits, with combination drug therapy often required for many patients to reach their blood pressure-reduction goals. Approximately one-third of hypertensive patients who seek treatment fail to reach their goals, either because they are resistant to drug therapy or stop treatment due to side-effect issues. A medical need exists for new antihypertensive agents with improved risk–benefit profiles. However, within the past decade, the economics of bringing a new antihypertensive agent to market have become challenging due to the plethora of generic drugs available, the advent of polypharmacology, and the difficulty of identifying agents that are better than the standard of care. Only a few new mechanistic classes of antihypertensive agents have been recently approved, suggesting a lack of innovation within the industry. In this review, we describe the results of a survey of drug companies and drug classes in the 2007–2009 antihypertensive patent literature and comment on the current state of innovation in antihypertensive drug discovery.